Pengaruh Pemberian Silase Rumput Odot dengan Level Jerami Padi Sebagai Absorban Terhadap Konsumsi Kecernaan dan Retensi Nitrogen Pada Ternak Kambing - Fangidae, Herru; Oematan, Gustaf; Amalo, Daud; Lestari, Gusti Ayu Y. (Yayasan Sumber Daya Manusia Cerdas, 2024)
This research aims to determine the effect of giving odot grass silage with rice straw as an absorbant on consumption, digestibility and nitrogen retention in goats. This research used a Latin square design (LSD) with 4 treatments and 4 periods as a repeat. The treatment is JP0 = silage 100% odot grass, JP10 = + silage 90% odot grass and rice straw 10%, JP20 = silage 80% odot grass and rice straw 20%, JP 30 = silage 70% odot grass and rice straw 30%. The parameters observed are nitrogen consumption, nitrogen digestibility, and nitrogen retention. The data obtained were analyzed using Analysis of variance. Based on the results of the study, the average Consumption of N (g/h/d) JP0: 12,677 JP10: 10,180 JP20: 9,486 JP30: 10,882. Digestibility average N (%) JP0 : 86,493 JP10: 88,918 JP20: 88,699 JP30: 87,576. Retention average N (g/h/d) JP0: 11,089 JP10: 8,574 JP20: 8,070 JP30: 8,469. Shows that the application of odot grass silage with rice straw as an absorbant has no real effect (P >0.05) on nitrogen consumption, nitrogen digestibility and nitrogen retention. The use of rice straw as an absorbant of up to 30% in the manufacture of odot grass silage did not affect the consumption of dry matter, organic matter and nitrogen and digestibility of dry matter, organic matter, nitrogen and nitrogen retention in goats.